Dinámica del nitrógeno en un gradiente de edad de Cistus ladanifer L. - Marquez M.; Nuñez E.; Escudero J.C. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
This study is an analysis of Nitrogen dynamics in populations of Cistus ladanifer L., of different ages, between 4 and over 40 years. For this purposes the Nitrogen contents of different fractions of aerial biomass were studied from each population: leaves, capsules and three types of stems chosen according to their diameters. The efficiency of internal Nitrogen recirculation was analysed by studying fallen leaf remainders classified into leaves, stems, capsules and flowers.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)